Vitamin A-fortified cooking oil reduces vitamin A deficiency in infants, young children and women: results from a programme evaluation in Indonesia. Issue 14 (16th January 2015) - Sandjaja,; Jus'at, Idrus; Jahari, Abas B; Ifrad,; Htet, Min Kyaw; Tilden, Robert L; Soekarjo, Damayanti; Utomo, Budi; Moench-Pfanner, Regina; Soekirman,; Korenromp, Eline L
Abstract: Objective: To assess oil consumption, vitamin A intake and retinol status before and a year after the fortification of unbranded palm oil with retinyl palmitate. Design: Pre–post evaluation between two surveys. Setting: Twenty-four villages in West Java. Subjects: Poor households were randomly sampled. Serum retinol (adjusted for subclinical infection) was analysed in cross-sectional samples of lactating mothers (baseline n 324/endline n 349), their infants aged 6–11 months ( n 318/ n 335) and children aged 12–59 months ( n 469/477), and cohorts of children aged 5–9 years ( n 186) and women aged 15–29 years ( n 171), alongside food and oil consumption from dietary recall. Results: Fortified oil improved vitamin A intakes, contributing on average 26 %, 40 %, 38 %, 29 % and 35 % of the daily Recommended Nutrient Intake for children aged 12–23 months, 24–59 months, 5–9 years, lactating and non-lactating women, respectively. Serum retinol was 2–19 % higher at endline than baseline ( P <0·001 in infants aged 6–11 months, children aged 5–9 years, lactating and non-lactating women; non-significant in children aged 12–23 months; P =0·057 in children aged 24–59 months). Retinol in breast milk averaged 20·5 μg/dl at baseline and 32·5 μg/dl at endline ( P <0·01). Deficiency prevalence (serum retinol <20 μg/dl) was 6·5–18 % across groups at baseline, and 0·6–6 % at endline ( P ≤0·011). In multivariate regressions adjusting for socio-economic differences, vitamin A intake from fortified oil predicted improved retinol status for children aged 6–59 months ( P =0·003) and 5–9 years ( P =0·03). Conclusions: Although this evaluation without a comparison group cannot prove causality, retinyl contents in oil, Recommended Nutrient Intake contributions and relationships between vitamin intake and serum retinol provide strong plausibility of oil fortification impacting vitamin A status in Indonesian women and children.